Academic Discourse in Polish Specialised Literature - Król-Kumor, Martyna (Respectus Philologicus, 2017)
The article is an attempt at reconstructing the concept of academic discourse based on the available Polish specialised literature.In result of analysis, it has turned out that the concept of academic discourse does not have a clear definition in Polish science yet and its name is often used as a synonym for scientific discourse and didactic discourse. The works dealing with academic discourse may generally refer to two areas of expertise: pedagogy and linguistics.The most significant research result of this article is coming up with the typology of academic discourse from pragmatic point of view. The following subtypes have been separated within academic discourse: scientific-academic discourse, didactic-academic discourse, educational-academic discourse, administrative-academic discourse and public-academic discourse. Each type of academic discourse has features which are common for all subtypes (they have the same place of discourse functioning and strict connection between discourse participants and an academic institution) as well as differentiating features, among which there is a purpose of activity within each subtype of academic discourse (purposes such as cognition, working out didactic methods, teaching, managing the university and creating a positive, favourable social image of the university).
Keywords: discourse; academic discourse; scientific discourse; didactic discourse; school discourse; typology of academic discourse